2020
DOI: 10.3390/atmos11020132
|View full text |Cite
|
Sign up to set email alerts
|

Spring Season in Western Nepal Himalaya is not yet Warming: A 400-Year Temperature Reconstruction Based on Tree-Ring Widths of Himalayan Hemlock (Tsuga dumosa)

Abstract: The Himalayan region has already witnessed profound climate changes detectable in the cryosphere and the hydrological cycle, already resulting in drastic socio-economic impacts. We developed a 619-yea-long tree-ring-width chronology from the central Nepal Himalaya, spanning the period 1399–2017 CE. However, due to low replication of the early part of the chronology, only the section after 1600 CE was used for climate reconstruction. Proxy climate relationships indicate that temperature conditions during spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Moreover, we comprehend that the reported decline in pre-monsoon surface temperature since the 1960s (Yadav et al, 2004) and concurrent increasing trend in pre-monsoon precipitation could be a consequence of evaporative cooling associated with regional vegetation greening (Shen et al, 2015). Multi-century temperature reconstructions from the adjacent western Nepal Himalayan region have also indicated that there is no increase in pre-monsoon temperature trends (Thapa et al, 2015;Aryal et al, 2020).…”
Section: Summer Season Amc and Mass Balancementioning
confidence: 77%
“…Moreover, we comprehend that the reported decline in pre-monsoon surface temperature since the 1960s (Yadav et al, 2004) and concurrent increasing trend in pre-monsoon precipitation could be a consequence of evaporative cooling associated with regional vegetation greening (Shen et al, 2015). Multi-century temperature reconstructions from the adjacent western Nepal Himalayan region have also indicated that there is no increase in pre-monsoon temperature trends (Thapa et al, 2015;Aryal et al, 2020).…”
Section: Summer Season Amc and Mass Balancementioning
confidence: 77%
“…Similarly, some glacier‐fluctuation episodes from the Gawalong glacier (1768, 1918) (Zhu et al, 2013), Lhamkoka glacier (1777, 1918), Gyalaperi glacier (1763) (Bräuning, 2006), Xinpu glacier (1746, 1927), Gongpu glacier (1910), Zepu glacier (1785), and Baitong glacier (1757) (Hochreuther et al, 2015) in the southestern Tibetan Plateau were closely synchronized with our moraine dating in the Manang valley in the central Himalayas. Furthermore, the periods with advancing glacier corresponded with cold intervals (1796–1874 and 1900–1936), as shown by tree ring‐based spring temperature reconstruction from the lower part of the Manang valley (Aryal et al, 2020), and from the southestern Tibetan Plateau (1892–1927 and 1958–1981) (Huang et al, 2019). The synchronization between ages of the dated moraines and higher snow accumulation epochs (Figure 6) implied that higher snow accumulation period may link with formation of moraines.…”
Section: Discussionmentioning
confidence: 92%
“…It has been successfully used to date moraines in the southeastern Tibetan Plateau (Bräuning, 2006; Hochreuther et al, 2015; Xu et al, 2012; Zhu et al, 2013), southern Chile (Koch & Kilian, 2005), Canadian Rocky Mountains (Luckman, 1993; Smith et al, 1995), European Alps (Holzhauser et al, 2005; Reinig et al, 2018), and Patagonian Andes (Masiokas et al, 2010; Meier et al, 2019). Most dendrochronological studies in the central Himalayas focused on tree growth responses to climate change or past climate reconstructions (Aryal et al, 2020; Cook et al, 2003; Liang et al, 2014, 2019; Panthi et al, 2020; Rai et al, 2019; Sano et al, 2005; Sigdel, Dawadi, et al, 2018; Thapa et al, 2015) or treeline dynamics (Sigdel, Wang, et al, 2018; Sigdel, Liang, et al, 2020). In spite of the dense forest cover observed on the LIA glacial deposits, little is known whether dendrochronology can be used to reconstruct glacier fluctuation events in the Himalayas.…”
Section: Introductionmentioning
confidence: 99%
“…In our study site, the MI is positive in the monsoon season in both future periods, meaning precipitation exceeds PET. Therefore, enhanced growth during the summer monsoon will likely be controlled by temperatures instead of rainfall, as evidenced by other studies (eg., Aryal et al., 2023; Aryal, Gaire, et al., 2020). As discussed above, cool and moist weather conditions encourage the occurrence of cluster1, significantly increasing the growth rate, especially in July and August.…”
Section: Discussionmentioning
confidence: 99%